Nitrogen-doped porous carbon from sucrose-polyaniline precursor co-processing: high CO2 adsorption performance and cyclic stability - Li Zhao; Run Zhang; Yong-sheng Ma; Zhong-hao Wu; Qi Niu; Xin-hua Yuan; Xin-yue Zhou; Kai Li; Qiang Lu (Biomass and Bioenergy, 2027)

Sp1 induces autophagic in epithelial ovarian cancer through inhibition of the PI3K/AKT/mTOR pathway - Yushuang Zheng; Xu Xu; Zheyu Lu; Wangzhi Li; Lu Wang; Run Luo; Keqi Xu; Fan Wang (Tissue and Cell, 2026)

Dead pine tree detection using an iterative semi-supervised framework integrating expert annotation and active learning - Xiaolin Li; Run Yu; Yu Qiu; Jianlong Luo; Xiaojian Lu; Shiguo Huang; Songqing Wu; Feiping Zhang (Computers and Electronics in Agriculture, 2026)

Structural features of endogenous polyphenols in modulating oxidative stability of tiger nut (Cyperus esculentus L.) oil: Insights from Rancimat and density functional theory - Zheng-Kai Zhang; Meng-Chen Xie; Jun-Chao Zhang; Lu-Han Sun; Xiao-Shuang Cai; Run-Yang Zhang; Guo-Qiang Zhang; Hua-Min Liu (Food Chemistry, 2026)

One-step fabrication of porous carbon via molten salt-assisted pyrolysis and evaluation of its CO2 adsorption performance - Li Zhao; Run Zhang; Ting Huang; Ding-wang Qiao; Qi Niu; Ze-jun Luo; Kai Li; Qiang Lu (Biomass and Bioenergy, 2026)

A new chlorine-containing flavanol and four new phenylpropanoids from Toddalia asiatica - Bing-Ying Zheng; Zhan-Tao Zhao; Feng Wu; Nan An; Shu-Qi Wu; Lu Gan; Sheng Yin; Run-Zhu Fan; Gui-Hua Tang (Natural Product Research, 2026)

ClO₂-induced VBNC state in Enterococcus faecalis poses a health risk in drinking water systems - Ziyi Zhang; Shuai Cheng; Menghua Duan; Yihong Wang; Weipeng Xu; Yiming Lu; Hui Yang; Na Lv; Run Ma; Jiahui Guo; Chao Shi (Journal of Hazardous Materials, 2026)

An in-situ photoderivative fluorescence enhancement method without chromatographic separation for Aflatoxin B1 (AFB1) detection - Wan Tian; Wenhui Cheng; Chuanliang Wang; Jiashan Lu; Shihao Lu; Run Zhang; Yanxia Qi; Yafeng Guan; Xuhui Geng (Journal of Hazardous Materials, 2026)

Hirsutanines H−O, monoterpene indole alkaloids from Uncaria hirsuta with neuroprotective effects - Nan An; Lei-Ming Wu; Shu-Qi Wu; Jia-Luo Huang; Dong Huang; Fang-Yu Yuan; Yi-Ling Liao; Run-Zhu Fan; Xian-Yuan Yang; Gui-Hua Tang; Lu Gan; Sheng Yin (Phytochemistry, 2026)

Co-assembled organic phosphorescent crystals with ultralong phosphorescence in high-temperature and water environment - Bin Li; Ziyi Lu; Wensheng Xu; Run Wang; Jiang Liu; Linshuo Jiang; Yin Xiao; Jianchao Ma; Yang Li; Xilong Yan; Bowei Wang; Ligong Chen (Chemical Engineering Journal, 2026)

Chloride Loss in Fine Aerosols over the Atmosphere of Pearl River Estuary - Yuan Gao; Jianbo Ye; Lili Ming; Run Lu; Jiayin Sun; Guizhen Fang; Yawei Xue; Yee Jun Tham (Aerosol Science and Engineering, 2026)

Whole-genome sequencing reveals the genetic diversity of Aeromonas from freshwater fish and the presence of novel genomic islands carrying clinically important antimicrobial resistance genes - Xiao-Qin Wang; Ke Wu; Run-Min Kang; Heng Lin; Lu-Ya Liu; Ting Xian; Yi-Zhi Tang; Xin Yang; An-Yun Zhang; Hong-Ning Wang; Chang-Wei Lei (Aquaculture, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Crustal growth and modification of the Muzidian Gneiss complex revealed by detrital zircon from modern river sediments - Xiao-Fei Qiu; Xi-Run Tong; Da Wang; Xin Deng; Shan-Song Lu (Chemical Geology, 2026)

Target Fibroblast-B cell crosstalk via MIF signaling drives pathogenic B cell differentiation and joint damage in knee osteoarthritis - Bizhi Tu; Zheng Zhu; Yan Li; Zhengming Zhu; Shijie Wang; Peizhi Lu; Ya Li; Shuo Yang; Dingtao Hu; Run Fang; Rende Ning (Inflammation Research, 2025)

Cluster-induced room-temperature phosphorescence of low-boiling-point non-conjugated organic small molecules - Li Gao; Wensheng Xu; Jiang Liu; Ligong Chen; Shengtian Wu; Run Wang; Ziyi Lu; Guoyi Bai; Bowei Wang (Chemical Engineering Journal, 2025)

Finite-time output feedback control of unmanned marine surface vessels with rotatable thrusters and propellers under deception attacks in an IoT environment - Xiangfei Meng; Guichen Zhang; Bing Han; Yanji Liu; Mengwei Chen; Run Lu (Ocean Engineering, 2025)

Two-step fabrication of perovskite films with controlled crystal orientation via PbI₂ modulation for high-performance solar cells - Yixuan Wang; Shuheng Jiang; Mengjin Zhang; Zequn Ma; Huishu Li; Run Zhao; Hao Lu (Chemical Engineering Journal, 2025)

Molecular docking screening of endogenous protease inhibitors in sea bass (Lates calcarifer) and in vitro validation of their inhibitory efficacy - Run-Jian Gao; Lu Sun; Sen-Di Zhou; Yu-Meng Liu; Wei-Qiang Qiu; Sheng-Ping Yang; Yun-Fang Qian (Food Bioscience, 2025)

Impact of collagen degradation on the textural quality of salmon (Salmo salar): A preliminary study from the perspective of endogenous collagenase and bacteria - Lu Sun; Run-Jian Gao; Cheng-Jian Shi; Andrew M. Hemmings; Yun-Fang Qian (Food Bioscience, 2025)

Restoration of secondary forest in the Greater Mekong Subregion struggles to offset primary forest carbon losses - Zongqi Peng; Yanhui Zhu; Kun Yang; Yi Luo; Xixi Lu; Jiasheng Wang; Yang Zhang; Danni Su; Run Sun; Mingfeng Zhang; Jingcong Ma; Yang Liu; et al. (Global and Planetary Change, 2025)

The association between greenspace exposure and sperm quality: A retrospective cohort study focusing on sperm kinematics and the influence of buffer settings - Sixuan Zeng; Tingting Yang; Run Tian; Xin Jin; Lu Zhang; Fuping Li; Leyao Fu; Jiarui Cai; Junhao Liao; Guishuang Song; Xiaoli Luo; Yujue Wang; et al. (Environmental Research, 2025)

Arbuscular mycorrhizal fungi enhance Leymus chinensis resistance to salinity predominantly through regulating root endosphere bacteria - Peiran Guo; Yazhou Hou; Bingbing Jia; Yuchen Wang; Chengyan Lu; Run Wang; Jiaying Lin; Yanan Zhang; Wei Guo; Frank Yonghong Li (Plant and Soil, 2025)

A critical review of human internal exposure to short-chain chlorinated paraffins and its concerning health risks - Ke Fang; Yi-bin Sun; Run-ming He; Jian-kun Qian; Wen Gu; Yi-fu Lu; Zhao-min Dong; Yi Wan; Chao Wang; Song Tang (Environmental Research, 2025)

Enhanced H2O2 production via Piezo-photocatalysis using BaTiO3/g-C3N4 S-scheme heterojunction - Ziwei Zhao; Ruixin Chen; Qi Ling; Kui Yan; Wei Gan; Yuqing Lu; Sheng Ding; Run Liu; Zhaoqi Sun; Miao Zhang (Journal of Environmental Chemical Engineering, 2025)

Characterization of β-cyclodextrin inclusion complexes embedded with lemongrass and basil essential oils and their modified sustained-release pads for large yellow croaker (Larimichthys crocea) fillet preservation - Yun-Fang Qian; Cheng-Jian Shi; Lu Sun; Run-Jian Gao; Sheng-Ping Yang (Food Bioscience, 2025)

Highly stretchable, anti-freezing, self-adhesion and self-healing zwitterionic hydrogel electrolytes for flexible electronic devices - Jingxuan Zheng; Jingye Liang; Jishuai Xu; Fangying Lu; Hanbin Yu; Yong Liu; Run Wang (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Boosting structural stability and air stability towards layered oxide cathodes for potassium ion batteries - Hong Chen; Lu-Kang Zhao; Xuejiao Cheng; Xuan-Wen Gao; Zhaomeng Liu; She-Dong Li; Dong-Run Yang; Tian-Zhen Ren; Wen-Bin Luo (Chemical Engineering Journal, 2025)

Adaptive Positioning Control of Multi-Point Moorings with Disturbance Observation Under Input Constraints - Run Lu; Guichen Zhang; Ru Liu; Chaojian Gao; Wei Chen; Huanglong Fu (Journal of Marine Science and Engineering, 2024)
In the presence of dynamic uncertainties, external time-varying disturbances, and limited inputs to the multi-point mooring system (MPMS) of a floating offshore platform (FOP), this paper proposes a robust adaptive dynamic surface (RADS) control method incorporating a disturbance observer. A disturbance observer is designed to estimate the unknown time-varying disturbance and apply feedforward compensation to the control variable. Simultaneously, the adaptive law of the σ-corrected leakage term is employed to estimate the bound of the disturbance observation error, thereby enhancing positioning accuracy. An auxiliary dynamic system (ADS) is then introduced to address input constraints, while the differential explosion problem associated with the traditional inversion method is resolved through the integration of the dynamic surface control (DSC) algorithm. The Lyapunov function is utilized to demonstrate that the controller ensures the consistent ultimate boundedness of all signals within the closed-loop system. Finally, a simulation experiment was conducted based on the eight-point mooring platform of the “Kantan3”, and the positioning accuracy reached 3%, which is higher than the specification requirements of the classification society. The results indicate that the designed controller achieves higher positioning accuracy and improved anti-interference performance and has been put into practical application on “Kantan3”.

Study on the thermo-hydraulic behaviors within a CiADS 61-pin wire-wrapped fuel assembly under porous blockage conditions based on LBEblockageFoam - Yun-Xiang Li; Run-Sheng Yang; Yue Li; Xing-Kang Su; Yi-Wen Han; Zi-Nan Huang; Lu Meng; Song Li; You-Peng Zhang; Lu Zhang; Wei Jiang (Annals of Nuclear Energy, 2024)

Dynamics of impure CO2 and composite oil in mineral nanopores: Implications for shale oil recovery and gas storage performance - Lu Wang; Run Zou; Yifan Yuan; Yifan Zhang; Rui Zou; Liang Huang; Yisheng Liu; Zhan Meng; Hao Chen (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Liquid metal micrometer fibers with chain-bead structure for precision sewing in smart textiles applications - Feng Xu; Huiyun Xiao; Yuanzhao Wu; Fali Li; Haifeng Zhang; Jinyun Liu; Zidong He; Shiying Li; Qi Zhang; Xingjian Lu; Jie Shang; Yiwei Liu; et al. (Chemical Engineering Journal, 2024)

Developing a regional scale construction and demolition waste landfill landslide risk rapid assessment approach - Huanyu Wu; Qiaoqiao Yong; Jiayuan Wang; Weisheng Lu; Zhaoyang Qiu; Run Chen; Bo Yu (Waste Management, 2024)

Overall and geographic pattern of incidence, fatality and mortality of sepsis among hospitalized non-child cancer patients in China: A nationwide cross-sectional study - Bin Lu; Yang Xu; Na Li; Yueyang Zhou; Xudong Ma; Yan Chen; Run Dong; Xiang Zhou; Min Dai; Hongda Chen; Li Weng; Bin Du (Science Bulletin, 2024)

Sustainable and efficient scouring/bleaching strategy for cotton fabric using sucrose octaacetate/peroxide activated system: Mechanistic insights, performance optimizations, and environmental benefits - Huiyu Jiang; Run Lu; Xin Xiao; Yan Liang; Jie Chen; Qing Li; Wen Zhang (Journal of Cleaner Production, 2024)

InNi3C0.5/Fe3O4 catalyst for the CO2 hydrogenation to methanol: Co-precipitation preparation, performance and mechanistic insight - Chao Meng; Wenli Gu; Bo Peng; Run Xu; Hao Wang; Tian Lan; Guofeng Zhao; Yong Lu (Fuel, 2024)

Internal electric field and oxygen vacancies synergistically boost S-scheme VO/BiOCl-TiO2 heterojunction film for photocatalytic degradation of norfloxacin - Ruixin Chen; Wei Gan; Jun Guo; Yuqing Lu; Sheng Ding; Run Liu; Miao Zhang; Zhaoqi Sun (Chemical Engineering Journal, 2024)

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

A novel stress concentration inspection method for marine oil and gas pipeline based on UNSM - Jiaxing Xin; Jinzhong Chen; Renyang He; Rui Li; Xiaolong Li; Chang Liu; Run-kun Lu; Zhengda Su; Wenbo Han (Ocean Engineering, 2024)

Advances in biotin biosynthesis and biotechnological production in microorganisms - Jia-Run Zhao; Si-Qi Zuo; Feng Xiao; Feng-Zhu Guo; Lu-Yi Chen; Ke Bi; Dong-Yuan Cheng; Zhi-Nan Xu (World Journal of Microbiology and Biotechnology, 2024)

Marine nitrogen cycling in the aftermath of the Marinoan Snowball Earth - Yawen Lu; Run Li; Zhenfei Wang; Zekun Meng; Xiqiang Zhou; Chao Chang; Xingliang Zhang; Kang-Jun Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Impacts of compound extreme weather events on summer ozone in the Beijing-Tianjin-Hebei region - Peilan Lu; Run Liu; Zheng Luo; Shiyi Li; Yanxing Wu; Wenzhao Hu; Xin Xue (Atmospheric Pollution Research, 2024)

Activated carbon-boosted BiOI in CO2 adsorption and electron transfer for photothermally catalyzed CO2 oxidative dehydrogenation of propane - Run-Qing Miao; Zhen-Hong He; Bao-Ting Wu; Jiajie Liu; Sen-Wang Wang; Kuan Wang; Weitao Wang; Lu Li; Zhao-Tie Liu (Chemical Engineering Journal, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Low-temperature dyeing performance of polylactic acid fabrics pretreated with natural deep eutectic solvent - Huan Qi; Jie Chen; Qing Suo; Run Lu; Yangyi Chen; Chuyang Zhang; Huiyu Jiang (Journal of Cleaner Production, 2024)

Petrological models of magma evolution on the formation of mafic-felsic igneous complexes of the Emeishan large igneous province, SW China - Ze-Run Xue; Peng-Fei Lu; Ping-Ping Liu; Ling-Min Zhang (Journal of Asian Earth Sciences, 2024)

Outdoor artificial light at night and male sperm quality: A retrospective cohort study in China - Run Tian; Tingting Yang; Chenghan Xiao; Fuping Li; Leyao Fu; Lu Zhang; Jiarui Cai; Sixuan Zeng; Junhao Liao; Guishuang Song; Chuan Yu; Ben Zhang; et al. (Environmental Pollution, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

Micro-mechanism insights into the adsorption of anionic dyes using quaternary ammonium-functionalised chitosan aerogels - Nan Du; Li-Yuan Huang; Yan-Shu Xiong; Run Tian; Jiang-Yu Yin; Dan-Yu Cao; Dong-Bin Hu; Hai-Qin Lu; Wen Li; Kai Li (Carbohydrate Polymers, 2023)

Synergistic mechanisms of bioorganic fertilizer and AMF driving rhizosphere bacterial community to improve phytoremediation efficiency of multiple HMs-contaminated saline soil - Chengyan Lu; Zhechao Zhang; Peiran Guo; Run Wang; Tai Liu; Junqing Luo; Baihui Hao; Yuchen Wang; Wei Guo (Science of The Total Environment, 2023)

Lower limits of petrophysical parameters for effective reservoirs in ultradeep carbonate gas reservoirs: A case study from the Deng IV Member, Gaoshiti-Moxi Area, Sichuan Basin, SW China - Lu Wang; Yifan Zhang; Ruilan Luo; Rui Zou; Hui Deng; Run Zou; Liang Huang; Yisheng Liu (Journal of Hydrology, 2023)

Eliminating temporal correlation in quantum-dot entangled photon source by quantum interference - Run-Ze Liu; Yu-Kun Qiao; Han-Sen Zhong; Zhen-Xuan Ge; Hui Wang; Tung-Hsun Chung; Chao-Yang Lu; Yong-Heng Huo; Jian-Wei Pan (Science Bulletin, 2023)

A crack characterization model for subsea pipeline based on spatial magnetic signals features - Jiaxing Xin; Rui Li; Jinzhong Chen; Run-kun Lu; Chang Liu; Zhengda Su; Renyang He; Hongwu Zhu (Ocean Engineering, 2023)

Bioorganic fertilizers improve the adaptability and remediation efficiency of Puccinellia distans in multiple heavy metals-contaminated saline soil by regulating the soil microbial community - Run Wang; Tai Liu; Chengyan Lu; Zhechao Zhang; Peiran Guo; Bingbing Jia; Baihui Hao; Yuchen Wang; Wei Guo (Journal of Hazardous Materials, 2023)

Variations in the concentration, source and flux of polycyclic aromatic hydrocarbons in sediments of the Pearl River Estuary: Implications for anthropogenic impacts - Yali Li; Nairong Guo; Ke Yuan; Baowei Chen; Junjie Wang; Maofeng Hua; Jing Yu; Jingyan Hu; Run Lu; Shichun Zou; Ying Yang (Science of The Total Environment, 2023)

Forest hydrology modeling tools for watershed management: A review - Ge Sun; Xiaohua Wei; Lu Hao; María González Sanchis; Yiping Hou; Rasoul Yousefpour; Run Tang; Zhiqiang Zhang (Forest Ecology and Management, 2023)

Effects of the probability of pulse-like ground motions on landslide susceptibility assessment in near-fault areas - Jing Liu; Hai-ying Fu; Ying-bin Zhang; Pei-yi Xu; Run-dan Hao; Hai-hong Yu; Yun-yong He; Hong-yan Deng; Lu Zheng (Journal of Mountain Science, 2023)

Gastrodin Attenuates Lipopolysaccharide-Induced Inflammatory Response and Migration via the Notch-1 Signaling Pathway in Activated Microglia - Yue-yi Yao; Run Li; Yan-ji Guo; Yu Zhao; Jia-zhi Guo; Qing-long Ai; Lian-mei Zhong; Di Lu (NeuroMolecular Medicine, 2022)

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

EPG-recorded Feeding Behaviors Reveal Adaptability and Competitiveness in Two Species of Bemisia tabaci (Hemiptera: Aleyrodidae) - Shao-hua Lu; Jing-jing Li; Run-e Bai; Feng-ming Yan (Journal of Insect Behavior, 2021)

High-precision downward continuation of potential fields algorithm utilizing adaptive damping coefficient of generalized minimal residuals - Zhi-Hou Zhang; Xiao-Long Liao; Ze-Yu Shi; Anthony R. Lowry; Yu Yao; Run-Qi Lu; Xiang-Tai Fan; Peng-Fei Liu; Si-Wei Zhao (Applied Geophysics, 2020)

Suppression of miR-30a-3p Attenuates Hepatic Steatosis in Non-alcoholic Fatty Liver Disease - De-Run Wang; Bing Wang; Ming Yang; Zhen-lu Liu; Jing Sun; Yan Wang; Hui Sun; Liang-Jun Xie (Biochemical Genetics, 2020)

Effects of Cr(VI) exposure on electrocardiogram, myocardial enzyme parameters, inflammatory factors, oxidative kinase, and ATPase of the heart in Chinese rural dogs - Jianwei Lu; Kangping Liu; Mengzhu Qi; Hao Geng; JiaJia Hao; Run Wang; Xiaona Zhao; Yongxia Liu; Jianzhu Liu (Environmental Science and Pollution Research, 2019)

Insight into the Dissolution Molecular Mechanism of Ternary Solid Dispersions by Combined Experiments and Molecular Simulations - Run Han; Tianhe Huang; Xinyang Liu; Xunqing Yin; Haifeng Li; Jiahong Lu; Yuanhui Ji; Huimin Sun; Defang Ouyang (AAPS PharmSciTech, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Upper-ocean dynamical features and prediction of the super El Niño in 2015/16: A comparison with the cases in 1982/83 and 1997/98 - Hong-Li Ren; Run Wang; Panmao Zhai; Yihui Ding; Bo Lu (Journal of Meteorological Research, 2017)

XCI-escaping gene KDM5C contributes to ovarian development via downregulating miR-320a - Yi-Xi Sun; Yi-Xin Zhang; Dan Zhang; Chen-Ming Xu; Song-Chang Chen; Jun-Yu Zhang; Ye-Chun Ruan; Feng Chen; Run-Ju Zhang; Ye-Qing Qian; Yi-Feng Liu; Lu-Yang Jin; et al. (Human Genetics, 2017)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Naturally p-Hydroxybenzoylated Lignins in Palms - Fachuang Lu; Steven D. Karlen; Matt Regner; Hoon Kim; Sally A. Ralph; Run-Cang Sun; Ken-ichi Kuroda; Mary Ann Augustin; Raymond Mawson; Henry Sabarez; Tanoj Singh; Gerardo Jimenez-Monteon; et al. (BioEnergy Research, 2015)

An Observational Study of Autologous Bone Marrow-Derived Stem Cells Transplantation in Seven Patients with Nervous System Diseases: A 2-Year Follow-Up - Chao Ren; Run-lu Geng; Wei Ge; Xiao-Yun Liu; Hao Chen; Mei-Rong Wan; De-Qin Geng (Cell Biochemistry and Biophysics, 2014)

Effect of Zinc Source on Performance, Zinc Status, Immune Response, and Rumen Fermentation of Lactating Cows - Run L. Wang; Jian G. Liang; Lin Lu; Li Y. Zhang; Su F. Li; Xu G. Luo (Biological Trace Element Research, 2013)

Improvement of acetic acid tolerance and fermentation performance of Saccharomyces cerevisiae by disruption of the FPS1 aquaglyceroporin gene - Jun-Guo Zhang; Xiu-Ying Liu; Xiu-Ping He; Xue-Na Guo; Ying Lu; Bo-run Zhang (Biotechnology Letters, 2011)

Effect of Dietary Supplementation with Copper Sulfate or Tribasic Copper Chloride on the Growth Performance, Liver Copper Concentrations of Broilers Fed in Floor Pens, and Stabilities of Vitamin E and Phytase in Feeds - Lin Lu; Run L. Wang; Zheng J. Zhang; Fred A. Steward; Xugang Luo; Bin Liu (Biological Trace Element Research, 2010)